The Role of Schools in Accessing Mental Healthcare for Children Exposed to Adult Intimate Partner Violence. - Chanmugam, Amy (Children & Schools, 2026)
This study illuminates the role schools play in access to mental healthcare for children exposed to adult intimate partner violence (IPV), a large and often invisible population with elevated risks for poor psychological adjustment and negative academic consequences. Schools are well positioned as potential service providers, or as gateways to providers. Mothers (N = 30) of school-age children residing in IPV shelters completed semistructured ethnographic interviews centered on their experiences accessing help for a "focus child," the child each mother identified as having the greatest emotional/behavioral challenges. Qualitative data were supplemented with standardized measures of maternal IPV experiences (Abusive Behavior Inventory) and the child's psychological adjustment (Strengths and Difficulties Questionnaire) and posttraumatic stress symptoms (Parent Report of Posttraumatic Symptoms). Mothers described numerous barriers to obtaining help for child mental health. Seventeen discussed interactions with their child's school during the process. Family–school interactions emerged as turning points shaping help-attainment trajectories, representing both impeding and facilitating roles. The article concludes with a discussion of the implications of these findings for practice.